New design and application for active and passive solar dryers in the Huetar Norte region of Costa Rica - Guzmán-Hernández, Tomás de Jesús (2021)
Thermal solar systems use solar radiation to heat a fluid, generally consist of solar collectors that absorb the light and a glass cover that protect installation and maintains the heat producing a greenhouse effect. Depends of the use and place conditions can present modifications. These systems can adapt in agricultural activities thus was implemented the modified hybrid forced active solar systems as well as autonomous passive systems in different agricultural and agro-industrial productive units in the Huetar Norte region of Costa Rica. Through a local pilot program, were financed by governmental institutions from 2016 to 19, with a view to improving the drying process of agricultural products compared to traditional systems. It is intended that, with the use of these systems, greenhouse gases will be reduced, locally and globally, and these systems are a clean production alternative that improves the energy efficiency of small and medium producers. The hybrid forced systems are equipped with computerized devices for data recording. The most current, it was designed and applied a radiant floor, and the passive was added a photovoltaic system of 1 K, which gives it autonomy. The results have made it clear, the production units that were benefited improved their production process by reducing working times and increasing the efficiency of the process the quality and safety of their products.